2023
DOI: 10.34305/jmc.v3i02.741
|View full text |Cite
|
Sign up to set email alerts
|

Korelasi Tingkat Stres Dan Pola Tidur Dengan Kebugaran Tubuh Mahasiswa Tingkat Akhir Di Stikes Kuningan

Abstract: Pada mahasiswa tingkat akhir yang sedang mengerjakan skripsi gangguan tidur paling sering terjadi karena tingkat stres yang tinggi bisa memicu menurunnya kesehatan. selain stres, pola tidur yang buruk  juga dapat mempengaruhi kebugaran tubuh seseorang. Laporan Riskesdas (2018) angka kejadian gangguan emosional (stres) pada kelompok usia ≥ 15 tahun sekitar 8,9%. Penelitian ini bertujuan untuk menganalisis hubungan antara stres dan pola tidur dengan kebugaran tubuh mahasiswa tingkat akhir program studi S1 Kepera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Similar studies have been conducted by (Moonti et al, 2023;Pangestika et al, 2018), But the study concluded that there was a significant relationship between sports activities, sleep quality, stress levels, and physical fitness. This research is a development of previous research to answer with certainty whether there is a relationship between physical fitness and sleep quality.…”
Section: Introductionsupporting
confidence: 52%
“…Similar studies have been conducted by (Moonti et al, 2023;Pangestika et al, 2018), But the study concluded that there was a significant relationship between sports activities, sleep quality, stress levels, and physical fitness. This research is a development of previous research to answer with certainty whether there is a relationship between physical fitness and sleep quality.…”
Section: Introductionsupporting
confidence: 52%